2020
DOI: 10.1093/joc/jqaa025
|View full text |Cite
|
Sign up to set email alerts
|

Instagram Inspiration: How Upward Comparison on Social Network Sites Can Contribute to Well-Being

Abstract: Passive exposure to others’ positive self-presentations on social network sites (SNS) such as Instagram has been repeatedly associated with reduced well-being, particularly by triggering upward social comparison and envy. However, prior research has largely neglected that upward comparisons on SNS may also facilitate positive outcomes, specifically media-induced inspiration, a motivational state highly conducive to well-being. We conducted two experiments that tested whether and how cognitive-affective process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
100
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 47 publications
5
100
0
5
Order By: Relevance
“…Although the conclusions of most reviews confirm the passive social media use hypothesis, several recent studies have demonstrated that browsing cannot only lead to envy, but also to inspiration (Meier et al, 2020;Meier & Schäfer, 2018) and enjoyment (Krasnova et al, 2015), which can both lead to positive rather than negative effects on well-being (Meier et al, 2020;Schueller & Seligman, 2010). In fact, SM-induced inspiration and enjoyment seem to be at least as common as SM-induced envy.…”
Section: Browsing Inspiration Enjoyment and Well-beingmentioning
confidence: 95%
See 4 more Smart Citations
“…Although the conclusions of most reviews confirm the passive social media use hypothesis, several recent studies have demonstrated that browsing cannot only lead to envy, but also to inspiration (Meier et al, 2020;Meier & Schäfer, 2018) and enjoyment (Krasnova et al, 2015), which can both lead to positive rather than negative effects on well-being (Meier et al, 2020;Schueller & Seligman, 2010). In fact, SM-induced inspiration and enjoyment seem to be at least as common as SM-induced envy.…”
Section: Browsing Inspiration Enjoyment and Well-beingmentioning
confidence: 95%
“…Envy is a painful and hostile emotion that arises when a person "lacks another's superior quality, achievement, or possession and either desires it or wishes that the other lacked it" (Parrott & Smith, 1993, p. 908). In some social media (SM) studies, a distinction is made between benign and malicious envy (e.g., Meier, Gilbert, Börner, & Possler, 2020;Wu & Srite, 2021), while others have focused only on malicious envy (e.g., Lin, van de Ven, & Utz, 2018). Whereas benign envy motivates us to try to achieve similar achievements or possessions as the person we envy, malicious envy makes us wish that the envied person lacks or does not deserve these achievements or possessions (van de Ven, Zeelenberg, & Pieters, 2009).…”
Section: Social Media Browsing Envy and Well-beingmentioning
confidence: 99%
See 3 more Smart Citations